User Engagement in Developing Use-Inspired Glacial Lake Outburst Flood Decision Support Tools in Juneau and the Kenai Peninsula, Alaska - Abdel-Fattah, Dina; Trainor, Sarah; Hood, Eran; Hock, Regine; Kienholz, Christian (Frontiers in Earth Science, 2021)
Glacial lake outburst floods (GLOFs) significantly affect downstream communities in Alaska. Notably, GLOFs originating from Suicide Basin, adjacent to Mendenhall Glacier, have impacted populated areas in Juneau, Alaska since 2011. On the Kenai Peninsula, records of GLOFs from Snow Glacier date as far back as 1949, affecting downstream communities and infrastructure along the Kenai and Snow river systems. The US National Weather Service, US Geological Survey, and University of Alaska Southeast (for Suicide Basin) provide informational products to aid the public in monitoring both glacial dammed lakes as well as the ensuing GLOFs. This 2 year study (2018–2019) analyzed how communities affected by the aforementioned GLOFs utilize these various products. The participants in this project represented a variety of different sectors and backgrounds to capture a diverse set of perspectives and insights, including those of homeowners, emergency responders, tour operators, and staff at federal and state agencies. In addition, feedback and suggestions were collected from interviewees to facilitate improvements or modifications by the relevant entities to make the informational products more usable. Findings from this study were also used to inform changes to the US National Weather Service monitoring websites for both Suicide Basin and Snow Glacier. This paper’s findings on GLOF information use are relevant for other GLOF-affected communities, from both an information user and information developer perspective.